THE INFLUENCE OF OUTDOOR SPACE SPATIAL ECOLOGICAL ENVIRONMENT FOR THE ELDERLY - Jing, Lu; Misni, Alamah (PLANNING MALAYSIA, 2024)
Outdoor activities improve the physical and mental health of the elderly. Only an excellent outdoor environment can attract the elderly, increase the frequency of their activities, and improve their quality. However, there is a lack of research on urban outdoor environmental factors that influence the outdoor activities of elderly people in China. This study aims to explore outdoor environmental elements suitable for the elderly in China, explore the impact of the environment on the activities of the elderly, and better design outdoor environments for the elderly. The study selected Beishan Park in Qingdao, China, as the research location because of its outdoor environment. It explored three aspects: the physical environment, the psychological environment, and the ecological environment. A survey questionnaire was written for data collection. The data was analysed using PLS-SEM to analyse the relationship between outdoor environmental factors. The research findings indicate that the ecological environment, which fosters both the physical and psychological environments, significantly influences the outdoor activities of the elderly population. A good ecological environment can encourage the elderly to spend more time outdoors. This paper discusses the important outdoor environmental factors that affect the outdoor activities of the elderly, provides a basis for improving the outdoor environment and outdoor activities of the elderly in Chinese cities, and also provides a reference for designers and related personnel.